PENERAPAN SANKSI ADAT MENGENAI PENABRAKAN HEWAN MASYARAKAT ADAT DAYAK BEKATIK DI KABUPTEN BENGKAYANG - NIM. A1012201161, ROBBYANSYAH (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Customary sanctions refer to consequences or punishments applied by a society or community based on the traditional rules and norms they adhere to. This sanction is used as a form of customary law enforcement against individuals or groups who violate the rules or norms that apply in that society. Customary sanctions play an important role in maintaining the rules and norms passed down from generation to generation in a society. Although often local in nature and lacking formal legal force, customary sanctions have a significant impact in maintaining order and harmony within a community.The problem of this research is: